Antimicrobial Peptides as Antibiotic Adjuvants: Overcoming Resistance through Multifaceted Mechanisms - K. S. Sritha; K. P. Naseera; Ammini Parvathi (Probiotics and Antimicrobial Proteins, 2026)

Characterization and genomic analysis of vB_CoeS_P1, a novel marine bacteriophage, and definition of the new family Estoviridae - Shruthi P K; Parvathi Ammini; Pradeep Ram Angia Sriram (Archives of Virology, 2026)

Spatial and temporal dynamics of prokaryotes in the Eastern Arabian sea - Shyla Hafza; Ammini Parvathi; P. M. Muhammed Iqbal; Valliyodan Sudheesh; C. K. Sherin; N. V. Harikrishnachari (Environmental Monitoring and Assessment, 2025)

Microbial distribution in Mudbank regions off Alappuzha, South-West coast of India - Jasna Vijayan; Parvathi Ammini; Angia Sriram Pradeep Ram; Maheswari Nair; Telesphore Sime-Ngando (Environmental Monitoring and Assessment, 2024)

Bacterial diversity in the aquatic system in India based on metagenome analysis—a critical review - Jasna Vijayan; Vinod Kumar Nathan; Parvathi Ammini; Abdulla Mohamed Hatha Ammanamveetil (Environmental Science and Pollution Research, 2023)

Diversity pattern of marine culturable heterotrophic bacteria in a region with coexisting upwelling and mud banks in the southeastern Arabian Sea - Jasna Vijayan; Parvathi Ammini; Vinod Kumar Nathan (Environmental Science and Pollution Research, 2022)

Influence of hydrological factors on bacterial community structure in a tropical monsoonal estuary in India - Ammini Parvathi; Michela Catena; Vijayan Jasna; Nikhil Phadke; Nikhita Gogate (Environmental Science and Pollution Research, 2021)

Survival of the blaNDM-harbouring Escherichia coli in tropical seawater and conjugative transfer of resistance markers - Susmita Mukherjee; Manjusha Lekshmi; Parvathi Ammini; Binaya Bhusan Nayak; Sanath H. Kumar (Archives of Microbiology, 2021)

Seasonal variations in viral distribution, dynamics, and viral-mediated host mortality in the Arabian Sea - Aparna Sreekumar; Parvathi Ammini; Jasna Vijayan; Pradeep Ram Angia Sriram; Sime-Ngando Telesphore (Marine Biology, 2021)

Optimization of urease production by Bacillus halodurans PO15: a mangrove bacterium from Poovar mangroves, India - Vinod Kumar Nathan; Jasna Vijayan; Ammini Parvathi (Marine Life Science & Technology, 2020)

Isolation and characterization of a moderately halophilic Marinobacter phage-host system from the Arabian Sea - Sreekumar Aparna; Ammini Parvathi; Arya Kaniyassery (Environmental Monitoring and Assessment, 2020)

Carbon Dioxide Sequestering Ability of Bacterial Carbonic Anhydrase in a Mangrove Soil Microcosm and Its Bio-mineralization Properties - Vinod Kumar Nathan; Parvathi Ammini (Water, Air, & Soil Pollution, 2019)

Diurnal variations in bacterial and viral production in Cochin estuary, India - Ammini Parvathi; Vijayan Jasna; Keshavan C. Haridevi; Sebastian Jina; Murali Greeshma; Jacob Breezy; Maheswari Nair (Environmental Monitoring and Assessment, 2013)

First description of a cyanophage infecting the cyanobacterium Arthrospira platensis (Spirulina) - Stéphan Jacquet; Xu Zhong; Ammini Parvathi; Angia Sriram Pradeep Ram (Journal of Applied Phycology, 2013)

16S rRNA-based bacterial diversity in the organic-rich sediments underlying oxygen-deficient waters of the eastern Arabian Sea - Baby Divya; Ammini Parvathi; P. A. Loka Bharathi; Shanta Nair (World Journal of Microbiology and Biotechnology, 2011)

Distribution of Putative Virulence Genes and Antimicrobial Drug Resistance in Vibrio harveyi - Ammini Parvathi; Dafini Mendez; Ciana Anto (Indian Journal of Microbiology, 2011)

Study of changes in bacterial and viral abundance in formaldehyde-fixed water samples by epifluorescence microscopy - Ammini Parvathi; Seetha Radhakrishnan; M. P. Sajila; Breezy Jacob (Environmental Monitoring and Assessment, 2011)

Comparative Virulence Genotyping and Antimicrobial Susceptibility Profiling of Environmental and Clinical Salmonella enterica from Cochin, India - Ammini Parvathi; Jasna Vijayan; Greeshma Murali; Preethi Chandran (Current Microbiology, 2011)

Prevalence and Heterogeneity of Hemolysin Gene vhh Among Hatchery Isolates of Vibrio harveyi in India - Ammini Parvathi; Jeffy George; Sanath Kumar (Current Microbiology, 2009)

Identification of a novel UDP-N-acetylglucosamine enolpyruvyl transferase (MurA) from Vibrio fischeri that confers high fosfomycin resistance in Escherichia coli - Sanath Kumar; Ammini Parvathi; Ricardo L. Hernandez; Kathleen M. Cadle; Manuel F. Varela (Archives of Microbiology, 2009)

A study on the effects of some laboratory-derived genetic mutations on biofilm formation by Listeria monocytogenes - Sanath Kumar; Ammini Parvathi; Jeffy George; Georg Krohne; Indrani Karunasagar; Iddya Karunasagar (World Journal of Microbiology and Biotechnology, 2009)

Molecular characterization of thermostable direct haemolysin‐related haemolysin (TRH)‐positive Vibrio parahaemolyticus from oysters in Mangalore, India - Ammini Parvathi; H. Sanath Kumar; Amarbahadur Bhanumathi; Masanori Ishibashi; Mitsuaki Nishibuchi; Indrani Karunasagar; Iddya Karunasagar (Environmental Microbiology, 2006)
Summary Pathogenic Vibrio parahaemolyticus strains producing either or both of a thermostable direct haemolysin (TDH) and a TDH‐related haemolysin (TRH) encoded by tdh and trh genes, respectively, are isolated at a low rate from the environment. However, recently we observed that a considerable percentage of APW (alkaline peptone water) enrichment broths of oysters collected off Mangalore India, were trh + , rather than tdh + by PCR. In order to further investigate the prevalence and genetic diversity of trh bearing V. parahaemolyticus in our coast, we attempted to isolate and characterize trh + V. parahaemolyticus from oysters. A total of 27 trh + strains were isolated during the period between March 2002 and February 2004, of which nine were also tdh + . All the trh + isolates were positive for urease phenotype. The isolates belonged to diverse phenotypes. In order to explore the possible presence of heterogeneity in the trh gene region among trh + V. parahaemolyticus , a 1.5 kb region around trh gene was PCR amplified and restriction digested using selected restriction enzymes. The whole genome comparison of strains was performed by randomly amplified polymorphic DNA PCR (RAPD PCR). The PCR‐RFLP results revealed fairly well conserved nature of the trh gene region studied in different serotypes. Though 11 strains were positive by PCR for a genomic fragment that has been reported to be amplified in pandemic strains, all strains were negative by group‐specific PCR (GS‐PCR), orf8 PCR and showed a different RAPD pattern compared with pandemic strains. The results suggest that genetically diverse V. parahaemolyticus carrying virulence genes are associated with the aquatic environment in this region.

Study of the occurrence of Vibrio vulnificus in oysters in India by polymerase chain reaction (PCR) and heterogeneity among V. vulnificus by randomly amplified polymorphic DNA PCR and gyrB sequence analysis - Ammini Parvathi; H. Sanath Kumar; Indrani Karunasagar; Iddya Karunasagar (Environmental Microbiology, 2005)
Summary The pathogenic bacterium Vibrio vulnificus is widely distributed in estuarine waters throughout the world. In this study, the presence of V. vulnificus in oysters was studied both by conventional culture and DNA‐based molecular technique. Following enrichment in alkaline peptone water (APW), the bacteria were lysed and a nested polymerase chain reaction (PCR) for vvhA gene was performed. The effect of duration of enrichment on the sensitivity of detection by PCR was evaluated. The organism was isolated from 43% of samples after 18 h enrichment in APW by conventional culture method. Nested PCR amplifying a fragment of vvhA gene detected the organism in 11%, 60% and 81% of samples following 0, 6 and 18 h of enrichment. All the biochemically identified V. vulnificus strains possessed vvhA gene and belonged to biotype 1. The genetic relatedness among the strains was studied by randomly amplified polymorphic DNA (RAPD) PCR and gyrB sequence analysis. The results suggest the presence of two distinct clonal groups of V. vulnificus in oysters in India. The study demonstrates, for the first time that gyrB sequence analysis could be used to study the genetic diversity of V. vulnificus .